SEWA MENYEWA LAHAN PERTANIAN DI DESA SARANG BURUNG KOLAM DALAM REKONTRUKSI AKAD PERSPEKTIF KOMPILASI HUKUM EKONOMI SYARIAH (KHES) - Yuliana Yuliana; Moh. Fadhil; Nanda Himmatul Ulya (Al-Aqad, 2025)
This study aims to: 1) Examine the practice of agricultural land leasing in Sarang Burung Kolam Village; and 2) Analyze the legal status of this leasing practice from the perspective of the Compilation of Sharia Economic Law (KHES). The research employs a qualitative field study approach with a descriptive design. Data were collected through interviews and documentation. Data validity was verified using triangulation methods. Data analysis followed an interactive model, comprising data reduction, data presentation, and conclusion drawing. The findings indicate that: 1) Agricultural land leasing in Sarang Burung Kolam Village is carried out under a two-crop seasonal system, namely musim tahun kacik (small-year season) and musim tahun basar (big-year season); 2) This leasing practice complies with the provisions stipulated in Chapter I, Article 20 of the Compilation of Sharia Economic Law (KHES) concerning the general terms of ijarah. Consequently, the practice can be categorized under Sharia law as an ijarah contract.